Geodynamic and magmatic evolution of the Kamyaran ophiolite complex, NW Iran: Tectonic transition from oceanic subduction to continental collision - Veisinia, Ayoub; Ebrahimi, Mohammad; Rahimzadeh, Bahman; Zhang, Zhiyong; Ahmadian, Jamshid; Esmaeili, Rasoul (Journal of Asian Earth Sciences: X, 2025)
The ophiolites in the Zagros orogen are relics of the Neo-Tethyan Ocean, which existed between the continents of Laurasia and Gondwana. There is much debate about the formation and evolution of the Neo-Tethyan Ocean. Knowledge on its pre-collisional tectonic evolution is of critical importance in precisely constraining its timing and history. The Kamyaran ophiolitic complex consists of several tectonically dismembered units including peridotite lenses and various gabbroic rocks as part of a Mesozoic ophiolitic belt extending from Kermanshah to Khoy in northwestern Iran. Mineral chemistry of the peridotites indicates that they underwent medium degree of partial melting (14–18%) and produced melts of MORB-like character in a suprasubduction setting with weak subduction-related signatures. The beginning of intra-oceanic subduction in the northeast margin of the Arabian plate caused metasomatism in the residual mantle of depleted peridotites. Gabbroic rocks display tholeiitic to calc-alkaline signatures with negative Nb, Th and Ti and positive Sr, Ba, U and Eu anomalies. Granular and pegmatoid gabbroic rocks with slight depletion of LREE and HREE pattern, crystallized from parental melts of N-MORB composition. This magma, characterized by negative Th, Nb, and Ti anomalies, was generated from depleted mantle. Pegmatoid gabbros are distinguished from granular gabbros by features such as more depleted REE, negative Th, Nb, Ti anomalies and lack of Eu positive anomalies. Microgabbroic dykes show N-MORB affinities and lack negative Nb and Ta anomalies. Geological and geochemical data suggest a transitional setting from oceanic island arc to continental arc following the closure of the Neo-Tethys. The complex is part of the supra-subduction zone ophiolite that emplaced during the collision of the Arabian and Iranian plateaus.